Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) prevents lipopolysaccharide (LPS)-induced, sepsis-related severe acute lung injury in mice - Takaoka, Yuki (Nature Publishing Group, 2014)
Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) is an energy metabolism-related enzyme in the glycolytic pathway. Recently, it has been reported that GAPDH has other physiological functions, such as apoptosis, DNA repair and autophagy. Some in vitro studies have indicated immunological aspects of GAPDH function, although there is no definite study discussing the advantage of GAPDH as a therapeutic target. Here, we show that GAPDH has an anti-inflammatory function by using a lipopolysaccharide (LPS)-induced, sepsis-related severe acute lung injury (ALI) mouse model, which is referred to as acute respiratory distress syndrome (ARDS) in humans. GAPDH pre-injected mice were protected from septic death, and their serum levels of proinflammatory cytokines were significantly suppressed. In lung tissue, LPS-induced acute injury and neutrophil accumulation were strongly inhibited by GAPDH pre-injection. Pulmonary, proinflammatory cytokine gene expression and serum chemokine expression in GAPDH pre-injected mice were also reduced. These data suggest the therapeutic potential of GAPDH for sepsis-related ALI/ARDS.